Major QTLs control resistance to Rice hoja blanca virus and its vector Tagosodes orizicolus - Romero, Luz Elena; Lozano Potes, Iván; Garavito, Andrea; Carabalí, Silvio J.; Triana Espinel, Mónica; Villareal, Natalia; Reyes, Luis; Duque E., Myriam Cristina; Martínez, César P.; Calvert, Lee A.; Lorieux, Mathias (Oxford University Press, 2014)
Rice hoja blanca (white leaf) disease can cause severe yield losses in rice in the Americas. The disease is caused by the rice hoja blanca virus (RHBV), which is transmitted by the planthopper vector Tagosodes orizicolus. Because classical breeding schemes for this disease rely on expensive, time-consuming screenings, there is a need for alternatives such as marker-aided selection. The varieties Fedearroz 2000 and Fedearroz 50, which are resistant to RHBV and to the feeding damage caused by T. orizicolus, were crossed with the susceptible line WC366 to produce segregating F2:3 populations. The F3 families were scored for their resistance level to RHBV and T. orizicolus. The F2:3 lines of both crosses were genotyped using microsatellite markers. One major QTL on the short arm of chromosome 4 was identified for resistance to RHBV in the two populations. Two major QTL on chromosomes 5 and 7 were identified for resistance to T. orizicolus in the Fd2000 × WC366 and Fd50 × WC366 crosses, respectively. This comparative study using two distinct rice populations allowed for a better understanding of how the resistance to RHBV and its vector are controlled genetically. Simple marker-aided breeding schemes based on QTL information can be designed to improve rice germplasm to reduce losses caused by this important disease.